3D Physical Modelling Study of Shield-Strata Interaction under Roof Dynamic Loading Condition. (10th February 2021) - Yang, Shengli; Yue, Hao; Song, Gaofeng; Wang, Junjie; Ma, Yanyao; Liu, Fengqi
Abstract : The dynamic hazards in the open face area caused by the impact load of the massive strong roof become increasingly severe with the increase in the cutting height of the longwall face and its depth of cover. Understanding the strata-shield interaction under the dynamic impact loading condition may relieve the dynamic hazards. In this paper, a 3D physical modelling platform is developed to study the interaction between the roof strata and the longwall shield under the dynamic impact load conditions. A steel plate is dropped to the coal face wall at a certain height above the immediate roof to simulate the free fall of the main roof and the dynamic impact loading environment. The occurrence of major roof falls is modelled at different height above the model and at different positions relative to the longwall faceline. The large-cutting-height and top-coal-caving mining methods are modelled in the study to include the nature of the immediate roof. The results show that the level of face and roof failures depends on the magnitude of the dynamic impact load. The position and height of the roof fall have an important influence to the stability of the roof and face. The pressures on the shield and the solid coal face are relieved for the top-coal-caving face as compared to the large-cutting-height face.